Pelatihan Tari Gambyong Sebagai Implementasi Budaya di Desa Wonosoco, Kecamatan Undaan, Kabupaten Kudus - Deswira Lintang Samodra; Dita Nana Nur Latifah; Fawwaz Farhanul Ihsan; Lathifah Wulandari; Muhammad Nur Faizin; Mukaromah Puji Lestari; Nisrina Maharani; Rahma Mustika Hadisaputri; Reyhan Bagus Wicaksana; Sherly Jesica Rorensia; Yusuf Fadly Wardana; Asep Purwo Yudi Utomo (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
The Gambyong dance has long been a part of the artistic traditions in Wonosoco Village, Undaan Subdistrict, Kudus Regency. This dance is not only seen as entertainment but also as an integral element in various traditional celebrations in the village. The Gambyong dance has been passed down from generation to generation. However, with the influence of modern culture, the younger generation's interest in their local heritage has begun to decline. To prevent the loss of the Gambyong dance due to the lack of successors from the next generation, a community service activity was initiated to train the residents of Wonosoco Village, especially elementary school children, to preserve this cultural tradition. After three weeks of training, the elementary school children in Wonosoco Village successfully understood and mastered the movements of the Gambyong dance. This training is beneficial in ensuring that the Gambyong dance in Wonosoco Village has young generations who can continue and preserve it, so the culture does not fade over time